2017
DOI: 10.1063/1.4977812
|View full text |Cite
|
Sign up to set email alerts
|

SiNx coatings deposited by reactive high power impulse magnetron sputtering: Process parameters influencing the residual coating stress

Abstract: The residual coating stress and its control is of key importance for the performance and reliability of silicon nitride (SiNx) coatings for biomedical applications. This study explores the most important deposition process parameters to tailor the residual coating stress and hence improve the adhesion of SiNx coatings deposited by reactive high power impulse magnetron sputtering (rHiPIMS). Reactive sputter deposition and plasma characterization were conducted in an industrial deposition chamber equipped with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…A particularly promising coating material is amorphous silicon nitride [16][17][18][19][20][21][22][23][24][25] as bulk silicon nitride was shown to be biocompatible [26][27][28][29][30] and slowly dissolves in water-based solutions [19,20,[31][32][33]. Small, soluble, and biocompatible wear particles have the potential to reduce the negative immune response and prolong the implant lifetime.…”
Section: Introductionmentioning
confidence: 99%
“…A particularly promising coating material is amorphous silicon nitride [16][17][18][19][20][21][22][23][24][25] as bulk silicon nitride was shown to be biocompatible [26][27][28][29][30] and slowly dissolves in water-based solutions [19,20,[31][32][33]. Small, soluble, and biocompatible wear particles have the potential to reduce the negative immune response and prolong the implant lifetime.…”
Section: Introductionmentioning
confidence: 99%
“…As can be seen, coatings deposited with a higher target power showed lower L C2 values. This was due to higher residual stresses resulting from a higher N content and the increase in Si-N bonds [45,48]. Moreover, these coatings showed a generally denser morphology (data not shown), which in turn contributed to increased residual stresses [66], as demonstrated previously [48].…”
Section: Adhesionmentioning
confidence: 51%
“…In previous studies, we reported that the addition of C altered the surface reactivity of silicon nitride and influenced the coating density and surface morphology [44,45]. In addition, we have shown that an increased N content results in a higher hardness and density [46][47][48]. In this study, we investigated the effect of N, C, Cr, and Nb content, as well as ion energy, on the properties of silicon nitride (SiN x )-based coatings for joint applications, with a focus on their wear performance in a hard-on-soft contact, since, as mentioned above, the counter surface in a joint implant is usually a polyethylene polymer.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Ganesan et al 15 demonstrate that it is possible to tune the optical and electrical properties of hafnium oxide, tungsten oxide, and tungsten oxynitride coatings by varying the HiPIMS pulse length and therefore the duty cycle. The deposition process parameters that can be used to tailor the residual coating stress in order to improve the adhesion of SiN x coatings deposited by reactive HiPIMS are investigated by Schmidt et al 16 The angular distribution of plasma parameters and the resulting thin film characteristics were explored for Ar/O 2 HiPIMS discharge while varying the under growth angles with respect to the target surface when growing the TiO 2 film. 11 The deposition rates were found to be the largest in the forward directions and decrease towards large inclination angles and thus a pronounced anisotropy in the film deposition process and of the deposited layer structure.…”
mentioning
confidence: 99%